A Cat Nap - Clay, Shannon (Zaner-Bloser, Inc.)
Pam. I am Pam. A cat. A sad, sad cat. I can pat a sad cat. I can go to Nan. A tag! A cat tag! My cat! My cat Tam! My cat can nap! A cat nap!
Keywords: Animal Stories